Characterisation of Groundnut Ringspot Virus and a Related Reassortant Orthotospovirus Infecting Adenium obesum Plants in Brazil - Bello, Vinicius Henrique; Nagata, Tatsuya; Marubayashi, Julio Massaharu; Krause‐Sakate, Renate [UNESP]; Júnior, José Evando Aguiar Beserra; Passador, Martha Maria; Rezende, Jorge Alberto Marques; Kitajima, Elliot Watanabe (Wiley, 2025)
ABSTRACT Genomic reassortment is a well‐documented process in multisegmented viruses, including members in the genus Orthotospovirus . Comparative analysis of partial fragments of the large (L), medium (M) and small (S) segments of two orthotospovirus isolates from Adenium obesum (known as desert rose) collected in Brazil showed a higher nucleotide similarity with groundnut ringspot virus (GRSV). However, genome sequence analysis of another isolate of orthotospovirus from A. obesum revealed a reassortment event involving GRSV and tomato chlorotic spot virus (TCSV) with L and M segments assigned to GRSV and S to TCSV (i.e., S TC M G L G ). The two GRSV isolates from A. obesum were not transmissible to any tested plants by mechanical inoculation, including A. obesum itself. In contrast, the S TC M G L G isolate was mechanically transmitted to a number of indicator plants but not to A. obesum . Furthermore, neither S TC M G L G nor GRSV isolates were able to overcome the Sw5 resistance gene in tomato.